An autopsy case of acute cor pulmonale and paradoxical systemic embolism due to tumour cell microemboli in a patient with breast cancer. (3rd October 2012) - Uga, Sayuri; Ikeda, Shuntaro; Matsukage, Sho-ichi; Hamada, Mareomi
Abstract : A 62-year-old woman was admitted to our hospital because of severe respiratory distress. Diagnostic imaging studies suggested the existence of inexplicable cor pulmonale. Although we immediately sought the aetiology of her severe condition, she died suddenly on the fourth day after admission. Postmortem autopsy revealed tumour cell microemboli in the small pulmonary arteries. In addition, tumour cell embolisation identical to that in primary breast cancer cells was also observed in microvessels in systemic multiple organs, such as the liver, brain, kidneys, spleen, uterus, bone marrow and adrenal glands—with simultaneous findings of peripheral infarction. Systemic tumour cell embolism mediated through the patent foramen ovale superimposed on pulmonary tumour cell emboli (PTCE) is considered to be the mechanism underlying inexplicable cor pulmonale. The rapid aggravation of her condition terminated in death.